CHARACTERISTIC OF CATFISH (Pangasius hypophthalmus) BALL WITH THE ADDITION OF BANANA’S HEART (Musa paradisiaca) ONCONSUMER ACCEPTANCE - Naibaho, Josua; Sari, N. Ira; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this research was to determine the characteristic of catfish(Pangasius hypophthalmus) ball with the addition of banana’s heart (Musaparadisiaca) on consumer acceptance. The method used in this research wasexperimental analysis, with 10% (B1), 15% (B2) and 20% (B3) of banana’s heartaddition. Parameter were measured on organoleptic test and proximate analysis(water content, protein, fat content and crude fiber). The result showed that theaddition of banana’s heart was significantly affect to organoleptic and proximatevalue. Based on the level of consumer acceptance, the addition 20% of banana’sheart to catfish ball was most likey by consumer acceptance,with (B3) 77 panelist(96,25%). The characteristicof this treatment was brilliant in appearance, oldbrown color, fishy flavor and compact texture, soft and smooth fiber, less of fishin taste with the water content 30,59%, protein content 34,22%, fat content 6,76%and crude fiber content 2,20%..Keywords : Catfish, meatball,banana’s heart